Local development and enviromental governance: Experienced from extractive industry in East Luwu, Indonesia - Umar Congge; Srirath Gohwong (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
All activities that are beneficial with the use of natural resources and the impact on the environment. Likewise with sustainable development that is intensively carried out without paying attention to the surrounding environment. Therefore, this study aims to look at PT Vale's mining activities from the perspective of Environmental Governance. This research is a descriptive qualitative research with data collection techniques in the form of observation, interviews and literature study. The results of this study are seen from four indicators, namely effective and robust as well as fair and responsive. Management effectiveness is assessed based on the joint commitment made by PT Vale and the local government in realizing sustainable mining practices. The principle of fairness and responsiveness can be realized in efforts to improve the socio-economic outcomes of people living in mining areas where the existence of PT Vale facilitates the community by opening up job opportunities, providing programs for coastal communities.